Diagnostic criteria currently proposed for "ictal epileptic headache": Perspectives on strengths, weaknesses and pitfalls. - Parisi, Pasquale; Verrotti, Alberto; Costa, Paola; Striano, Pasquale; Zanus, Caterina; Carrozzi, Marco; Raucci, Umberto; Villa, Maria Pia; Belcastro, Vincenzo (Seizure, 2015)
PURPOSE: When we published the diagnostic criteria for "ictal epileptic headache" in 2012, we deliberately and consciously chose to adopt restrictive criteria that probably underestimate the phenomenon, rather than spread panic among patients and physicians who are reluctant to accept this entity. METHODS: Here we discuss four intriguing clinical cases to highlight why we believe, to this day, that it is necessary to follow these restrictive diagnostic criteria. CONCLUSIONS: EEG is not recommended as a routine examination for children diagnosed with headache, but it is mandatory and must be carried out promptly in cases of prolonged headache that does not respond to antimigraine drugs, if epilepsy is suspected or has been diagnosed previously. This is not a marginal or irrelevant question because possible isolated, non-motor, ictal manifestations should be taken into account before declaring that an epileptic patient is "seizure free" so as to ensure that any decision taken to suspend anticonvulsant therapy is safe.